2016
DOI: 10.1016/j.aninu.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pantothenic acid on growth performance, slaughter performance, lipid metabolism, and antioxidant function of Wulong geese aged one to four weeks

Abstract: This experiment was conducted to study the effects of pantothenic acid on the growth performance, slaughter performance, lipid metabolism, and antioxidant function of one-to four-week-old Wulong geese and determine the appropriate supplemental level of pantothenic acid. A total of 360 one-day-old Wulong geese were randomly divided into 6 groups with 6 replicates per group and 10 geese (5 males and 5 females) per replicate. The geese in group Ⅰ (control group) were fed a basal diet, and the geese in groups Ⅱ to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 10 publications
6
30
0
2
Order By: Relevance
“…Balancing copper (Cu) and zinc (Zn), though vitally important, may not be as easy as expected. Copper is an essential constituent of the growing number of cuproenzymes and copper metalloprotein with functions as diverse as electron transfer (Cobine et al, 2006 ;Festa and Thiel, 2011), pigmentation (Sendovski et al, 2011;Xu et al, 2013) and oxidation resistance (Wang et al, 2013;Ladomersky and Petris, 2015). Ayyat and Marai (2000) reported that supplementing rabbits with 100, 200 or 300 Zn mg/kg diet significantly increased live weight gains, but had no effect on feed intake, feed conversion ratio compared to control animals or those fed 400 Zn mg/kg diet.…”
Section: Introductionmentioning
confidence: 99%
“…Balancing copper (Cu) and zinc (Zn), though vitally important, may not be as easy as expected. Copper is an essential constituent of the growing number of cuproenzymes and copper metalloprotein with functions as diverse as electron transfer (Cobine et al, 2006 ;Festa and Thiel, 2011), pigmentation (Sendovski et al, 2011;Xu et al, 2013) and oxidation resistance (Wang et al, 2013;Ladomersky and Petris, 2015). Ayyat and Marai (2000) reported that supplementing rabbits with 100, 200 or 300 Zn mg/kg diet significantly increased live weight gains, but had no effect on feed intake, feed conversion ratio compared to control animals or those fed 400 Zn mg/kg diet.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its involvement in primary metabolic pathways, pantothenic acid de ciency (PAD) causes growth depression, skin lesions, diarrhea, loss of hair in mammals such as rats, cats, and pigs [2][3][4][5][6]. Also in poultry studies, PAD results in growth retardation, dermatosis, rough feathers, and high mortality in chicks, turkeys, geese, and ducks [7][8][9][10][11][12][13]. It has been demonstrated extensively that PA can keep the structure of intestine integrity and maintain the intestinal function of animals [3,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is shown that pantothenic acid could protect the cell membrane against damage caused by lipid peroxidation [22][23][24]. Previous studies have shown that dietary PAD could lead to oxidative stress in geese [9] and sh [21]. It is proposed that oxidative stress induced by PAD leads to intestinal injury and hypofunction.…”
Section: Introductionmentioning
confidence: 99%
“…It also serves as a cofactor for structural as well as catalytic properties of various enzymes such as lysyl oxidase, superoxide dismutase cytochrome oxidase, ceruloplasmin, dopamine hydroxylase and tyrosinase (Tang et al, ; Watanabe, Kiron, & Satoh, ). It is also reported to play an important role in collagen synthesis (Lall, ), pigmentation (Sendovski, Kanteev, Ben‐Yosef, Adir, & Fishman, ), electron transfer (Cobine, Pierrel, & Winge, ) and oxidation resistance (Wang et al, ). Dietary copper improves growth and immunological functions in diverse fish species (Gatlin & Wilson, ; Hameid et al, ; Lin, Shie, & Shiau, ; Mohseni, Pourkazemi, & Bai, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…an important role in collagen synthesis (Lall, 2002), pigmentation (Sendovski, Kanteev, Ben-Yosef, Adir, & Fishman, 2011), electron transfer (Cobine, Pierrel, & Winge, 2006) and oxidation resistance (Wang et al, 2013). Dietary copper improves growth and immunological functions in diverse fish species (Gatlin & Wilson, 1986;Hameid et al, 2017;Lin, Shie, & Shiau, 2008;Mohseni, Pourkazemi, & Bai, 2014;Wang et al, 2016).…”
mentioning
confidence: 99%